PENGARUH KOORDINASI DAN PENGAMBILAN KEPUTUSAN KEPALA SEKOLAH TERHADAP EFEKTIVITAS PENGELOLAAN DANA BOS DI SEKOLAH DASAR - Erna Erna; Wahyudi Wahyudi; Masluyah Suib (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThe research entitled "The Effect of Coordination and Principal Decision Making on the Effectiveness of BOS Fund Management in Pontianak State Elementary School". In this research used descriptive method with quantitative approach in comparative causal form. The result of the research that was tested by multiple linear regression analysis technique through SPSS (Statistical Package For Service Solutions) version 16 concluded that: 1) there is a coordination effect on the effectiveness of BOS management in SDN Kota Pontianak; 2) there is a decision-making effect on the effectiveness of BOS management in SD Negeri Kota Pontianak; 3) there is a mutual influence between coordination and decision-making on the effectiveness of BOS management so that the hipothesis which reads "there is a significant relationship between coordination and decision making on the effectiveness of BOS management in SD Negeri Kota Pontianak" is accepted. The study also recommends that: 1) the timing of BOS funds should be timely, as the delay in BOS funds affects school operations, the BOS funds provided to schools should be increased in number, keep the school operational activities very large, and reinforce them to the school committee, especially those concerned duties and functions of the committee; 2) the next researcher who wants to do research on the problem of BOS fund management, is expected to be able to analyze other wider subject, to be able to compare the effectiveness of BOS fund management more clearly. In addition, this research can be developed because every year the rules that apply in the management of BOS funds continue to grow. Keywords:Coordination, Decision Making, Effectiveness Management of BOS.